198k views
5 votes
I need help and steps of how u got it

I need help and steps of how u got it-example-1
User Yogurtearl
by
5.1k points

1 Answer

6 votes

Answer:

A) 4

Explanation:

There are a couple of ways to get this but this is how I did it:

1. Multiply the second equation by 1/4 to get the same fraction for y as the one in the first equation

1/4 x + 1/8 y = 2

1/4 (1/3 x + 1/2 y = 4)

1/12 x + 1/8 y = 1

2. Subtract the first equation from the new equation

1/12 x + 1/8 y = 1

- 1/4 x - 1/8 y = -2

-1/6 x= -1

3. Divide both sides by -1/6

-1/6 x= -1

-1/6 -1/6

x = 6

4. Substitute 4 in for x in the original equation:

1/4 (6) + 1/8y = 2

6/4 + 1/8y = 2

1/8y = 1/2

y = 4

User Paul Stanton
by
5.0k points